COMPARATIVE STUDY BETWEEN GENDER IN CHOOSING THE EFFECTIVE WAY TO SUPPORT THE GO GREEN CAMPAIGN AMONG HIGHER EDUCATION LEVEL STUDENTS - Muhammad Hasifullah Ibrahim; Lee Siu Ping; Nor Adibah Asmi; Nurul Amira Shamsuddin; Amir Hamzah Sharaai (PERINTIS eJournal, 2021)
The present study is to identify the effective way to support the Go Green campaign among higher education level students based on their gender. The targeted population for this research is the students of Universiti Putra Malaysia (UPM) in Serdang. Currently, in Malaysia, there are a lot of initiatives taken to increase the awareness of environmental issues among the public. Thus, UPM has joined in with the effort of trying to save the environment in many possible ways. Among the activities that are being carried out in UPM are promoting to use bicycles instead of cars, reducing the uses of polystyrene and also reducing the uses of plastic bag by constantly reminding the students about the effects that they have on the environment. In determining the most effective way to support the Go Green campaign, a group of students is selected randomly to be the sample of this study. The amount of sample taken is 269 students to represent the whole population. They were to choose what activity that they mostly prefer to do in supporting the campaign through the questionnaire distributed based on the objective of the research. The data collected are analyzed using Chi Square test which shows that there is a significant difference (X² = 23.149, df = 7, p < 0.05). Finally, the difference in choosing the effective way in supporting the Go Green campaign based on the gender of the students have been determined and it showed that the male students chose car pooling with standard residual value of 3.5, which is the highest value of the results.